Genetically derived effective population size estimates of herpetofaunal species should be used with caution. Issue 2 (9th December 2022) - Kimble, Steven J. A.; Unger, Shem D.; Williams, Rod N.
Abstract: Effective population size ( N E ) is an important parameter for conservation of threatened wildlife. Current estimators of N E that use genetic data, however, may not be equally useful among taxa that are difficult to sample, such as cryptic, iteroparous, long‐lived herpetofauna. To better understand the use of N E estimators for such taxa, we generated and compared contemporary N E estimates to evaluate methods, repeatability, and the effects of sample size at management scales and functional genetic population scales for the eastern box turtle ( Terrapene carolina carolina ) and eastern hellbender ( Cryptobranchus alleganiensis alleganiensis ). We chose these 2 species for their differing dispersal abilities, reproductive variances, and natural history traits, which may be useful in exploring the weaknesses and strengths of N E estimators. We collected species‐specific microsatellite genotypes from 2, 712 individuals (1, 133 hellbenders, 1, 579 box turtles) in 2007–2011 from across their ranges in the eastern United States. We then grouped samples into range‐wide genetic clusters, state‐level management populations, and small regional management populations (e.g., state parks). We also randomly subsampled (rarefied) from these 3 categories to explore the effects of reduced sampling effort on N E estimates. We used 4 popular estimators: NEESTIMATOR (linkage disequilibrium and heterozygote excess methods), LDNE, and ONESAMP. Over half of all attempts at estimating N E failed to give complete estimates (those that included only non‐negative and non‐infinity values). There was variation between species but also among estimators. Repeated sampling of genetic populations resulted in inconsistent results, and estimates generally increased with sample size. The linkage disequilibrium version of NEESTIMATOR returned the largest percentage (95.8%) of complete estimates. Program ONESAMP obtained complete estimates for 62.0% of attempts and generally provided the numerically largest estimates. Only 19.4% of LDNE estimates and none of the heterozygote excess version of NEESTIMATOR estimates were complete. Generally, N E estimates were higher for box turtles, perhaps because of their greater dispersal capabilities, historically larger populations, and longer lifespans. Our results suggest that estimates of N E for long‐lived herpetofauna species vary according to species, sample size, genetic cluster, management population, and estimator used. Therefore, we recommend managers of populations of long‐lived herpetofaunal species use N E estimators with caution, and consider results from multiple methods before incorporating N E into management practice. Abstract : Effective population size is an important parameter for conservation management of threatened populations that is easily calculated from genetic data. We tested 4 commonly used estimators on multiple populations of 2 herpetofaunal species with differing natural histories and found large variation between species and across estimators, high variation across replicate samples, and substantial effects of sample size on estimates. We recommend population managers consider multiple estimators, assess the effects of sample size, and use resulting estimates of effective population size with extreme caution.